Structural characteristics of the superior venae cavae wall at the intrapericardium segment in adults and aging individuals - Piffer, C. R. [UNESP]; Piffer, M. I S [UNESP]; Santi, F. P. [UNESP]; Dayoub, M. C O [UNESP] (My University, 1996)
The authors admit that the conjunctive-muscular constitution of the walls of the superior venae cavae throughout the length of the intrapericardium segment and the debouchement in the right atrium, associated with the presence of a myocardium sheath can be made up of a functional device of sphincter form able to act on the control of the blood flow to the interior of the arterial chamber as well as stopping blood flow during the arterial systole. The fixation of the venous wall to the deep chamber of the serous pericardium, contributes to growth in resistance during the elevation of venous pressure, making possible the preservation of integrity of the superior venae cavae. The expansion of fasciculi of nodal fibers in the right wall of the superior venae cavae permits that the unlocked impulse in the S-A node also reaches the vascular wall contributing to the shortening and diminution in caliber of the vein.
Keywords: Crista terminalis; Heart; Sinoatrial node; Sphincter; Superior venae cavae; Veins; adult; aging; female; heart; heart atrium; histology; human; male; middle aged; pericardium; physiology; superior cava vein; ultrastructure; Adult; Aging; Female; Heart Atria; Humans; Male; Middle Aged; Pericardium; Vena Cava, Superior